Competitiveness Between Countries: an analysis of patents data in the petrochemical industry - Garrido, Eduardo Cardoso (2019)
The data resulting from monitoring allow to indicate which countries present best conditions for investment in the technological world scenario and, thus, subsidize actions aimed at the development of business. The objective of this work was to verify if the technological investment by patents of the petrochemical industry is linked to the competitiveness of a country. Questel Orbit was used to search and analyze data contained in patent publications. Different indicators were used to carry out the analysis: GDP PPC; number of patents with priority claims in a country; and the GCI. There was a strong link between the number of patent deposits with GDP PPC and the level of investment in R&D. However, although a country is highlighted in relation to the mentioned indicators, this correlation is not applicable to all countries. There is a strong presence of China, USA and Japan in the context of patent publication.